Pelatihan Fisik Berlebih Meningkatkan Indeks Apoptosis pada Hepatosit Tikus (Rattus norvegicus) Wistar Jantan - Pangkahila, Elionardo; Linawati, Ni M.; Sugiritama, I. W.; Siswanto, Ferbian M. (Jurnal Biomedik : JBM, 2019)
Abstract: Excessive physical training or overtraining can increase the production of free radicals such as peroxide, superoxide, and hydroxyl radicals. These free radicals can cause apoptosis of various organ cells, including liver. This study was aimed to prove that overtraining led to hepatocyte apoptosis in male Wistar rats (Rattus norvegicus). This was an experimental laboratory study. Samples were 16 healthy male Wistar rats, aged 2.5-3 months, weighing ±200 grams, which were divided into 2 groups (n= 8 rats), as follows: control group (P0) and treatment group (P1). The control group was not given any treatment (sedentary lifestyle) meanwhile the treatment group was given overtraining (60 minutes of swimming, 7 times a week for 3 weeks). After 3 weeks of treatment, all rats were euthanized with ketamine to obtain the liver specimens. The apoptotic index was examined in histopathological slides with HE staining, 3 fields of views each, at 400 times magnification. The results showed that excessive physical training increased the apoptotic index in hepatocyte cells by ~700%. The apoptosis index in the P0 group was 0.78±0.31%, whereas in the P1 group was 5.42±0.44% (p<0.001). In conclusion, overtraining leads to apoptosis in the hepatocytes of male Wistar rats.Keywords: overtraining, apoptosis, hepatocytes Abstrak: Pelatihan fisik berlebih dapat meningkatkan produksi radikal bebas seperti radikal peroksida, superoksida, dan hidroksil. Radikal bebas ini dapat berlanjut menyebabkan apoptosis berbagai sel-sel organ, termasuk hati. Penelitian ini bertujuan untuk membuktikan bahwa pelatihan fisik berlebih dapat meningkatkan indeks apoptosis pada hepatosit tikus (Rattus norvegicus) Wistar jantan. Pada penelitian ini digunakan 16 ekor tikus wistar jantan berumur 2,5-3 bulan dengan berat badan ±200 gram dan sehat, dibagi menjadi 2 kelompok (n= 8 ekor) yaitu kelompok kontrol (P) dan perlakuan (P1). Kelompok kontrol tidak diberikan perlakuan sedangkan kelompok perlakuan diberi pelatihan berlebih. Setelah 21 hari perlakuan, tikus dieuthanasi dengan menggunakan ketamin untuk diambil organ hati. Indeks apoptosis diperiksa pada sediaan histopatologik dengan pewarnaan Hematoksilin Eosin (HE) pada 3 lapang pandang pembesaran 400x. Hasil penelitian menunjukkan bahwa pelatihan fisik berlebih meningkatkan indeks apoptosis pada hepatosit sebesar ~700%. Indeks apoptosis pada kelompok P0 ialah 0,78±0,31%, sedangkan pada kelompok P1 ialah 5,42±0,44% (p<0,001). Simpulan penelitian ini ialah pelatihan fisik berlebih meningkatkan indeks apoptosis pada hepatosit tikus Wistar jantan.Kata kunci: pelatihan fisik berlebih, apoptosis, hepatosit